The Revitalization of Islamic Education in the Modern Era from the Perspective of Syekh Naquib Al-Attas - Khaliza, Suci Noor Asa; Abidah, Aniqah Laili; Ahmad, Zainal Arifin; Hasanat, Inayatul (Southeast Asian Journal of Islamic Education, 2025)
Islamic education in the modern era faces several critical challenges, including the secularization of knowledge, curriculum dichotomy, and the degradation of moral and spiritual values. These issues have undermined the philosophical foundations of Islamic education and weakened the integration between religious and secular sciences. This study aims to explore the thoughts of Syekh Muhammad Naquib Al-Attas on the revitalization of Islamic education by focusing on three key aspects: the foundational concept of Islamic education, the challenges it faces in the contemporary context, and the strategies for its revitalization. Using the Systematic Literature Review (SLR) method, 636 articles were initially identified through Google Scholar and Crossref using the Publish or Perish software. After applying strict inclusion criteria and using the PRISMA protocol, 24 peer-reviewed journal articles published between 2019 and 2025 were selected for thematic analysis. The findings are categorized into three major themes: (1) the concept of ta’dīb as a holistic educational framework that integrates intellect, ethics, and spirituality as the core of Islamic education; (2) contemporary challenges, including the fragmentation of knowledge, moral degradation, and the dominance of secular epistemologies; and (3) strategic responses such as the Islamization of knowledge, curriculum integration, and educational reform based on tawḥīd. The results affirm the relevance of Al-Attas’s educational philosophy as a comprehensive paradigm for shaping insān kāmil, a balanced human being, and for reforming Islamic education in a way that remains spiritually grounded while addressing modern demands.